Relative efficiency of positive selection and tissue culture for generating pathogen-free planting materials of yam (dioscorea spp.) (2017)
Yams are staples in West Africa. They are propagated from tubers in an informal seed system. This encourages a build-up of diseases, and necessitates the rapid development of a formal seed system where certified seeds are functional. Although few reports exist on the use of meristem culture to generate pathogen-free yam, the success rate for the most economically important species in the sub-region, Dioscorea rotundata, for the most prevalent viruses is inadequate. To generate pathogen-free yam planting materials, the relative efficiency of tis¬sue culture and positive selection was compared. Twenty-one asymptomatic yam plants were positively selected from 8187 stands of five landraces. Five of these stands were tested virus-negative by multiplex polymerase chain reaction (PCR) for Yam mosaic virus (YMV), Yam mild mosaic virus (YMMV) and Cucumber mosaic virus (CMV), and by PCR for the genus Badnavirus (BV), giving 0.08% success. Single nodes of the positively selected stands were used to establish in vitro plantlets, which were screened onto bacteriological indexing medium. The same was done for meristem- and node-derived plantlets of the improved variety TDr 95/19158. Incidence of endophytes ranged from 18 to 32% in the nodal plantlets while it was 0% in the meristem-derived plantlets. The effect of meristem culture combined with thermotherapy on the virus infection status was deter¬mined using virus-tested, one week old in vitro plantlets of eight improved genotypes. These in vitro plantlets were incubated at 36 ± 0.5°C and 16 h photoperiod for 21 days, after which meristems were excised, regenerated into plantlets and re-tested for viruses. Seventy-three percent of the samples were recovered from YMV but the effect on BV was inconsistent. Positive selection can be used as a palliative in generating quality declared seed but meristem culture combined with thermotherapy is more efficient for generating certified seed tubers of yam.